2022
DOI: 10.1371/journal.pone.0265901
|View full text |Cite
|
Sign up to set email alerts
|

Silencing LncRNA CASC9 inhibits proliferation and invasion of colorectal cancer cells by MiR-542-3p/ILK

Abstract: Colorectal cancer (CRC) ranks the third in cancers and the second in the reasons of cancer-related death. More evidence indicates that long non-coding RNA participates in tumor initiation and progression. It’s known that cancer susceptibility candidate 9 is an oncogenic long non-coding RNA in CRC. miR-542-3p is a negative regulator of CRC, while integrin-linked kinase could contribute to tumor progression and chemoresistance. However, the correlation among long non-coding RNA cancer susceptibility candidate 9,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Prior studies have revealed a strong correlation of CASC9 with hepatocellular carcinoma, breast cancer, osteosarcoma, and pancreatic cancer progression[26-29] and its role in enhancing tumor resistance to ge tinib and gemcitabine [30][31][32]. However, Liu and Zhang et al noted contrasting ndings and reported that CASC9 silencing suppressed colon cancer cell proliferation and invasion [33,34]. The risk signature for cuproptosis in colon cancer patients includes ZEB1-AS1 and SNHG7 [35,36], while ATP2A1-AS1 was incorporated into the lncRNA-based prognosis prediction model for cuproptosis in patients with cervical cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have revealed a strong correlation of CASC9 with hepatocellular carcinoma, breast cancer, osteosarcoma, and pancreatic cancer progression[26-29] and its role in enhancing tumor resistance to ge tinib and gemcitabine [30][31][32]. However, Liu and Zhang et al noted contrasting ndings and reported that CASC9 silencing suppressed colon cancer cell proliferation and invasion [33,34]. The risk signature for cuproptosis in colon cancer patients includes ZEB1-AS1 and SNHG7 [35,36], while ATP2A1-AS1 was incorporated into the lncRNA-based prognosis prediction model for cuproptosis in patients with cervical cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…BBOX1-AS1 promotes the progression of CRC by acting as a sponge for hsa-miR-361-3p and upregulating SH2B1 ( 75 ). Silencing CASC9 can not only downregulate AKT3 expression by reducing the competitive binding of CASC9 with miR-576-5p, thereby inhibiting CRC cell proliferation ( 210 ), it can also inhibit the proliferation of CRC cells through the miR-542-3p/integrin-linked kinase pathway ( 80 ), CCAT2 is highly overexpressed in microsatellite stable CRC and can enhance tumor growth by activating the WNT signaling pathway through the CCAT2/miR-17-5p/TCF7L2 axis ( 86 ). Studies have found that by overexpressing or knocking down CCAT2, reducing CCAT2 can increase miR-145, thereby inhibiting the proliferation of cancer cells ( 211 ).…”
Section: Regulation Of Cell Proliferation By Lncrnasmentioning
confidence: 99%
“…Zhang et al. discovered that the CASC9/miR-542-3p/integrin-linked kinase regulatory axis is involved in the invasion and migration of CRC cells ( 80 ). The upregulation of CCAT1 expression promotes cell proliferation and invasion ( 83 ).…”
Section: Lncrnas Regulate Invasion and Metastasismentioning
confidence: 99%
“…The lncRNAs cancer susceptibility candidate 9 (CASC9) and small nucleolar RNA host gene 6 (SNHG6) can positively regulate the TGF-β pathway in CRC. CASC9, in particular, increases the stabilization of TGF-β2 mRNA[ 75 ], and a study by Zhang et al [ 76 ] showed that it targets miRNA-542-3p and could also increase chemoresistance. The lncRNA SNHG6, on the other hand, targets miR-26a-5p and increases the resistance of CRC cells to 5-fluorouracil (5-FU).…”
Section: Lncrnas As Regulators In Crcmentioning
confidence: 99%